(untitled) (Semiárida, 2021)
.). The present study evaluated the antioxidant capacity and content of phenolic compounds of the raw and dry leaf of Guaviduca (Piper carpunya Ruiz & Pav.), being the antioxidant capacity determined by the FRAP method (Ferric ion reducing antioxidant Power) and ABTS (Acid 2,2 –Azinobis (3ethylbenzothiazolin) 6sulfonic), and the content of total phenolic compounds using the FolinCiocalteau method, as a result we show that there is a high phenolic activity in essential oils obtained from wet leaves as well as the total antioxidant activity by the FRAP and ABTS method. In conclusion, we determined that the antioxidant capacity obtained by the 2 methods FRAP and ABTS is correlated with the content of total phenols.